Математичне моделювання процесу механічного вилучення олії з насіння рицини - Журавель, Дмитро Павлович; Дідур, Володимир Володимирович; Білоконь, Ярослав Васильович; Zhuravel, Dmytro; Didur, Volodymyr; Bilokin, Yaroslav (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті розглянуто питання оцінювання математичної моделі процесу механічного вилучення олії з насіння рицини. Дослідження проводились з використанням теорії консолідації пористих середовищ та закону фільтрації рідин, а визначення можливостей її застосування для пресів безперервної дії. Експериментальні випробування проводилися з використанням переривчастого та безперервного механічних пресів при різних температурних і силових режимів. У ході роботи встановлено, що проникність твердої структури насіння істотно впливає на ефективність екстракції, а підвищення температури сприяє інтенсифікації процесу завдяки зменшенню в’язкості олії. /// EN: The article considers the issue of evaluating the mathematical model of the process of mechanical extraction of oil from castor seeds. The research was conducted using the theory of consolidation of porous media and the law of liquid filtration, and the determination of the possibilities of its application for continuous presses. Experimental tests were conducted using intermittent and continuous mechanical presses under different temperature and force regimes. In the course of the work, it was established that the permeability of the solid structure of the seeds significantly affects the extraction efficiency, and an increase in temperature contributes to the intensification of the process due to a decrease in the viscosity of the oil. The transformation of the physical properties of the material during mechanical compression of oilseeds plays a decisive role in explaining the mechanisms underlying the oil extraction process. One of the key parameters is the permeability of the solid structure of the seed, since it largely determines the efficiency of oil separation under compressive loading. The main technological factors that affect this indicator are pressure, temperature and compression duration tcp. The results of the experiments showed that the permeability coefficient k increases with increasing temperature. Practical experience shows that heating the raw material during extraction contributes to the intensification of oil removal, as a result of which a higher product yield is ensured for the same compression time. Presumably, this dependence is associated with a decrease in oil viscosity at higher temperatures. This effect is most pronounced at the initial stage of compression, in the range tcp, typical for standard continuous presses. In particular, in approximately 5 seconds, more than 60 % of the total mass of oil can be removed, while at tcp = 20 s, its volume at elevated temperature sometimes exceeds the indicators of the lowtemperature regime by 2–3 times. The variability of this pattern is partly explained by the influence of the extraction pressure, which at a constant tcp usually causes a decrease in the permeability k. At the same time, within the studied compression time interval, this factor does not demonstrate a significant effect on the total volume of oil obtained, although its value may increase with shorter load cycles. Regarding the use of the mathematical model proposed by Bargail, the results obtained give reason to believe that the lower limit of tcp, considered in the experiments, may affect the sensitivity and reliability of the modeling for processes with a longer compression duration. At the same time, it was found that for tcp = 5 s the discrepancy between the experimental and calculated data is relatively small and does not exceed 30 %. Improving the compliance of the model with the real operation of the studied press is possible by adjusting the initial integration time (tint). In fact, the selection of such a value of this parameter, at which the difference between the predicted and experimental results is minimal, can be considered as an effective way to adapt the mathematical description of the process. The improved calculation algorithm opens up opportunities for detailed analysis of changes in the efficiency and productivity of press equipment under different operating modes. Thanks to this, the model can be used as a practical tool for optimizing machine parameters and achieving specified production indicators.
Mathematical modeling of the process of mechanical extraction of oil from castor seeds
Keywords: математична модель; насіння рицини; механічне пресування; екстракція; фільтрації рідин; консолідація пористих середовищ; mathematical model; castor seeds; mechanical pressing; extraction; liquid filtration; consolidation of porous media